The influence of the international monetary fund (IMF) on economic liberalization development in Egypt: A geopolitical and economic analysis (2011-2018) - Saudia, Rikh Rezza (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: International Monetary Fund (IMF) as an international financial institution implements a liberalism policy for countries that need loan funds. In 2016 after lengthy negotiations and numerous rejections from the public, the Egyptian Government finally made an agreement with the IMF. This agreement is the first agreement after the revolution in Egypt in 2011, which was also assessed as a result of implementing IMF policies. Egyptian society feels that the policies set by the IMF did not bring prosperity evenly. The influence of the IMF on the implementation of economic liberalization policies then becomes an interesting thing to study. Methods: This study aims to analyze the background and influence of the IMF on the development of economic liberalization in Egypt and explain how Egypt implements the policies set by the IMF. This research is a qualitative research with a descriptive analytical approach. Findings: The theory that will be used in this research is the institutional neoliberal theory developed by Robert Owen Keohane and elaborated with the concept of interdependence. Conclusion: This research concludes that the negotiation agreement between the IMF and Egypt in 2016 is because the Egyptian economy is in a state of decline. And the program agreement that was agreed with the IMF as an international organization had an influence on Egypt both in monetary, fiscal and structural terms. Novelty/Originality of this article: This study reveals that Egypt's IMF-backed reforms stabilized the economy but primarily benefited the elite, while the poor faced harsher conditions. Despite these negative social impacts, Egypt continued the reforms due to its interdependence with the IMF.